1993
DOI: 10.1111/j.1600-0722.1993.tb01128.x
|View full text |Cite
|
Sign up to set email alerts
|

Mandibular condyle lesions related to age at onset and subtypes of juvenile rheumatoid arthritis in 15‐year‐old children

Abstract: The severity of lesions in the temporomandibular joint (TMJ) area and their association with age at onset, the various forms of juvenile rheumatoid arthritis (JRA), and certain serologic tests for rheumatoid factor (RF), antinuclear antibodies (ANA), and human leukocyte antigen (HLA)‐B27 were determined in 15‐yr‐old children. The series comprised 121 JRA children, 78 girls and 43 boys, in whom an analysis had recently been made of the relation of TMJ lesions to jaw movement and occlusal status. The mean age at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
1
7

Year Published

2005
2005
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 31 publications
(40 citation statements)
references
References 24 publications
2
30
1
7
Order By: Relevance
“…The temporomandibular joint (TMJ) is frequently subject to inflammatory disorders in children especially within the disease pattern of juvenile idiopathic arthritis (JIA) [1][2][3][4][5][6][7][8][9]. Arthritis of the TMJ, if not detected early and treated properly, may lead to bone destruction and osseous deformation of the mandibular condyle resulting in growth disturbances and dysmorphic facial features [2; 10-12].…”
Section: Introductionmentioning
confidence: 99%
“…The temporomandibular joint (TMJ) is frequently subject to inflammatory disorders in children especially within the disease pattern of juvenile idiopathic arthritis (JIA) [1][2][3][4][5][6][7][8][9]. Arthritis of the TMJ, if not detected early and treated properly, may lead to bone destruction and osseous deformation of the mandibular condyle resulting in growth disturbances and dysmorphic facial features [2; 10-12].…”
Section: Introductionmentioning
confidence: 99%
“…International erkranken jährlich zwischen 2 und 20/100.000 Kinder und Jugendliche unter 16 Jahren (Quelle: Internetpräsenz GKJR, Gesellschaft für Kinder-und Jugendrheumatologie, Stand 11/2010; http://www.agkjr.de/jiahaeufigkeit.html). Etliche Studien konnten zeigen, dass 38−72% der jungen JIA-Patienten bereits einen klinisch nachweisbaren Befall eines oder beider Kiefergelenke haben [19,23,31,32]. Diese arthritische Schädigung der Kondylen kann Auswirkungen auf die Unterkieferentwicklung haben, weshalb etwa 30% der JIA-Kinder eine Mikrognathie zeigen, während eine Malokklusion im Allgemeinen rund 70% dieser Patienten betrifft.…”
Section: Methodsunclassified
“…The literature contains contradictory information on the prevalence of temporomandibular joint involvement in JIA. While Cannizzaro et al [7] observed that patients with a pauciarticular type were more frequently affected by temporomandibular joint changes than those with other subtypes, other groups of authors [16,19,29,35,44] found that patients with polyarticular manifestations were significantly more often affected than children with an pauci- von Bremen J, Ruf S Craniofacial modifications by JIA [19] could not find an association between HLA-B27 and arthritic temporomandibular joint involvement, Cannizzaro et al [7] and Pedersen [35] found that HLA-B27-positive patients had significantly less pathological TMJ changes than patients without HLA-B27. This inconsistency clearly illustrates that not only the JIA subtype needs to be defined, but also a differVeränderungen betroffen ist, kann aufgrund der uneinheitlichen und äußerst unübersichtlichen Datenlage nicht geklärt werden.…”
Section: Jia Subtype and Temporomandibular Joint Involvementmentioning
confidence: 99%
See 2 more Smart Citations